EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL DI MTS NEGERI 1 KOLAKA - Abdul Rahim (Guru Membangun, 2023)
The aim of the research is to know the effectiveness of digital class users in the MTs Neg environment. 1 Kolaka. This research method includes collecting data and looking for valid information. This research uses a qualitative approach based on the results of field research, to reveal and explore information. The informants used were Indonesian and Mathematics subject teachers. Data sources were obtained through documentation and observation of informants. Observations were carried out by direct observation, while information about digital learning was obtained through open interviews. Documentation is carried out by taking pictures while learning activities in the digital classroom are taking place. The research design is phenomenology or real conditions regarding the use of digital learning in locations. The analytical approach is through case studies at the research location. The research data is then processed and discussed in the form of a descriptive narrative. The research results show that the application of digital media in learning Indonesian and mathematics at MTs Neg. 1 Kolaka uses powerpoint slides containing material and videos about the lessons/material being presented. Evaluation is carried out e-digitally connected to the internet, namely CBT. The advantages of using digital media are that it activates the class atmosphere, lessons are less distracting, students are not bored and learning is effective. The disadvantages of using digital media are network constraints and sudden power outages. Based on the research results, it can be concluded that learning using digital media has been proven to be effective in learning.